(3fRgI GdfahS heVMc GdYHhSs - (3Ydj Hf ShOhf GdLQcSj GdjTHZGhj GdbGgQj , GHf ShOhf , CHh GdMSf,J (B868 (3g` s
(3ChdgG (B:s
(3CeG HYO, adeG cfJ aj MGd GdUZQ SGcf GdbdH ef JMQjc gqe GdYjGd aJQcJ gPg GdUfGYI deG QCjJgG cGSOI s
(3BNQgG (B:s
(3CQLh GdcQje deG bO bdJ eZaQI Ef GdcQje def jQLhg ZaGQ bGd eDdagG Efg Cfgi Pdc aj s
(3JYGhQ YdjgG CcKQ ef fGSNs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI JJab aj ChdgG eY GdfSNI GdChdis
(3HGNJdGa aj HYV GdCdaGX s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B292 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B106 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B734s
Keywords: (3GdCOHs